Floristic composition of Jahangirnagar University Campus - A semi-natural area of Bangladesh (Bangladesh Journal of Plant Taxonomy, 2021)
This study represents comprehensive taxonomic information on current floristic composition in the semi-natural campus area of Jahangirnagar University. This study reveals that this campus area harbours a total of 917 species belonging to 574 genera and 145 families of vascular plants. 70.34% of these species are wild and the rest are cultivated/planted. 63.79% of the species are native and 36.21% are exotic to Bangladesh. Pteridophytes and Gymnosperms are represented by 22 and 12 species, respectively, whereas, Angiosperms by 883 species. Magnoliopsida (dicotyledons) and Liliopsida (monocotyledons) are composed of 618 and 265 species, respectively. The family Poaceae with 89 species is the largest, which is followed by Fabaceae with 44 species and Asteraceae with 40 species. Most of the species are herbs (56.16%) and growing in diverse habitats. All species are economically or ecologically important, but mostly as medicinal, ornamental, fodder and forage, fruit, vegetable, timber and fuel wood. The study area houses 15 plant species, previously listed as threatened to Bangladesh. Thus, the study area is floristically rich in respect to its number of plant species belonging to different groups and its size. This area might serve as a campus-based excellent center of biodiversity conservation by strengthening the existing management and adopting necessary policies and strategies.Bangladesh J. Plant Taxon. 28(1): 27-60, 2021 (June)